2022
DOI: 10.1177/09544062211070716
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on mechanical and microstructural evolution of stationary shoulder friction stir welded aluminum alloy AA7075-T651

Abstract: The stationary shoulder friction stir welding (SSFSW) technique promotes new opportunities for welding material. In the current work, a special setup of SSFSW was designed and manufactured in only three parts according to the homemade friction stir welding (FSW) machine dimensions and specifications. This setup with minimum parts is easily adjustable beside it facilitates fast control of the tool pin length. This gives the design more advantages than the previous designs published for the same purpose. Two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…According to previous works [ 3 , 25 , 26 ], three distinct regions develop in the FSSWed area, namely the SZ, the thermo-mechanically affected zone (TMAZ), and the heat-affected zone (HAZ). These three regions are characteristic of the cross-sectional joints processed with friction stir processing (FSP) [ 28 , 29 ], FSW [ 30 ], and FSSW [ 3 , 8 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to previous works [ 3 , 25 , 26 ], three distinct regions develop in the FSSWed area, namely the SZ, the thermo-mechanically affected zone (TMAZ), and the heat-affected zone (HAZ). These three regions are characteristic of the cross-sectional joints processed with friction stir processing (FSP) [ 28 , 29 ], FSW [ 30 ], and FSSW [ 3 , 8 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TMAZ at the bottom of the specimens exhibits minimum values of 100 HV on the retreating side (RS). Research by Hammad et al [29] on AA7075-T651 confirmed cross-sectional hardness symmetry when employing stationary shoulder friction stir welding, which allows for a reduction in surface heat input and uniformity of heat distribution. The HAZ and TMAZ demonstrate the minimum hardness between welding zones and vary in size based on the SD.…”
Section: Hardness Distributionmentioning
confidence: 92%
“…Table 3 summarizes the FSW program for AA7075-T6 butt joints. Based on investigations on the parameters of employing FSW in AA 7075-T651 by [23,29,30,37] it is concluded that changing the TS and SD will affect welding quality. The FSW machine used in the experimental work was the Model: EG-FSWM1, Suez University, Suez, Egypt [38].…”
Section: Experimental Procedures 21 Starting Materials Tool Design An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the hardness values increased with increasing the travel speed from 50 to 300 mm/min using all the pin geometries. This hardness trend is likely due to the decrease in heat input with increasing travel speed [20,37,38]. The decrease in the heat input will result in colder plastic deformation conditions which suppress the grain coarsening upon dynamic recrystallization and result in a significant grain size reduction in the processed zone.…”
Section: Mechanical Propertiesmentioning
confidence: 99%